Exploring Well-Being in Thoroughbred Horse Breeding: A Systematic Narrative Review Applying the PERMA+4 Framework - Claire McDonald; SarahJane Cullen; Siobhan O'Connor; Shane Noonan-Holohan; Giles Warrington; Jennifer Pugh; Adrian McGoldrick; Carol Nolan; Ciara Losty (International Journal of Equine Science)
Background: Staff shortages in the horseracing industry may impact horse and staff well-being. Working conditions such as a high workload, and poor work-life balance are found to influence staff retention. Thoroughbred breeders and staff work long hours with limited job control. However, there is a dearth of research examining breeding staff well-being. Aims: This article aims to explore associations between working conditions and well-being in thoroughbred horse breeders and stud farm staff. Materials and methods: A search of studies published up to January 2025 and available in PubMed, Scopus, and PsycINFO was performed and is reported in line with PRISMA-S.  Included articles were deductively coded into predetermined themes using the PERMA+4 framework for work-related well-being (positive emotions, engagement, relationships, meaning, accomplishment, physical health, work environment, mindset, and economic security). Results: A total of 21 studies were included for narrative analysis spanning the United States, United Kingdom, Australia, and Ireland. Results suggest that physical and psychosocial working conditions on stud farms may negatively impact staff well-being and retention through poor work-life balance, employee relations, and training and progression opportunities. Well-being may be influenced through the PERMA+4 dimensions of relationships, accomplishment, physical health, and work environment. Conclusion: This review demonstrates that the PERMA+4 model may be used as a theoretical framework to understand associations between working conditions and well-being in thoroughbred breeding work. Further research on the application of positive organizational psychology in this sector may increase understanding of and enhance staff well-being and retention.